THE USE OF CROSSWORD PUZZLE GAME MEDIA TO INCREASE STUDENT LEARNING MOTIVATION IN THE SUBJECT OF IPAS GRADE V UPTD SD NEGERI 33 PAREPARE - Shasliani, Shasliani; Sultan, Muhammad Asrul; Jusuf, Githa Pramesti (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research is motivated by the low learning motivation of students in grade V at UPTD SD Negeri 33 Parepare. The objective of this research is to enhance the learning process and motivation of students using crossword puzzle game media. The approach used in this research is qualitative. The type of research used is Classroom Action Research (CAR). The subjects in this research amounted to 24 students consisting of 10 male students, 14 female students, and a teacher. This research was conducted in 3 cycles. Each cycle was held 1 meeting with four stages, namely planning, implementation, observation, and reflection. Data collection was carried out using observation, documentation, and questionnaire techniques. The data were analyzed using data condensation techniques, data presentation, and conclusion drawing. This research focuses on the learning process and student learning motivation. The results of the research in cycles I and II showed that the learning process was in the category of sufficient (C) and student learning motivation was in the category of sufficient learning motivation. Meanwhile, in cycle III, the learning process was in the good (B) category, and student learning motivation was in the high learning motivation category. Thus, it can be concluded that the application of crossword puzzle game media increases the learning process and motivation of students in the IPAS subject in grade V at UPTD SD Negeri 33 Parepare.